EFISIENSI PENGGUNAAN FAKTOR PRODUKSI PADA USAHA TANI JAMUR TIRAM (Pleurotus ostreatus Jacq.) - Dedi Sufyadi; Cancan Gunawan Apidianur (Universitas Galuh Ciamis, 2020)
This study aims to determine the factors of production that affect oyster mushroom farming and analyze the level of efficiency of the use of production factors on oyster mushroom farming in UPT Agriculture Area Sukaraja. The method used in this research is survey with explorative descriptive approach. The data used are primary data secondary data obtained through interviews, questionnaires and literature study. The results analsis show a total coefficient value of 2.143. This value indicates the scale of oyster mushroom production is in phase I or increasing return to scale (IRS). The value of the coefficient of determination (R2) is 92.3 percent means that 92.3 percent of oyster mushroom production can be explained by variable use of production factors, while the remaining 7.7 percent is influenced by other variables besides the use of production factors not included in the model. The use of production factors that significantly influence the variation of oyster mushroom production are land and sawdust. While seeds, bran labor polybag, lime, paralon ring, rubbe and paper have no significant effect.